Mohs micrographic surgery - Nouri, Keyvan (Springer London, 2012)
The incidence of skin cancer is 3.5 million per year and accounts for more than fifty percent of all cancers combined, the majority of which are basal cell and squamous cell carcinomas. Mohs surgery has become the treatment of choice for certain basal cell and squamous cell carcinomas and other cutaneous tumors, with a high cure rate and low recurrence rate.  Physicians in all of the major disciplines of medicine will encounter patients with cutaneous cancers whom have undergone Mohs surgery or may need it in the future. Mohs Micrographic Surgery has been written to serve as a tool to build a foundation of the fundamentals of Mohs surgery. Each chapter is easy to read, with summary boxes of all the major points.  The chapters are written by world-renowned physicians in their respective specialties.  Overall, the reader will enjoy an up-to-date, reliable source of information on all important aspects of Mohs surgery, and will obtain a detailed understanding of this surgery, which will greatly benefit patient care.